1991
DOI: 10.1007/bf00852829
|View full text |Cite
|
Sign up to set email alerts
|

Expressing glomerular filtration rate in children

Abstract: We have reviewed the studies that provide the current standards of reference for glomerular filtration rate (GFR) in normal children from 14 days to 12 years of postnatal age. These standards currently are presented as ml/min per 1.73 m2, i.e., adjusted to average adult body surface area. Children from birth to 1 year of age have adjusted values below the adult range, making comparisons of observed to reference values difficult. Currently, there is no accepted way of obtaining reference values that vary smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 28 publications
2
45
0
4
Order By: Relevance
“…Normally, children will not reach a GFR of 100 until 1 y of age [Table S2, which also reports effective renal plasma flow (ERPF) measured as clearance of para-aminohippuric acid (PAH) (22) and serum creatinine levels (23)] (see also ref. 24). This interpretation of the data does not exclude the possibility that the slit-diaphragm acts as a molecular sieve, but it questions whether this action is required.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, children will not reach a GFR of 100 until 1 y of age [Table S2, which also reports effective renal plasma flow (ERPF) measured as clearance of para-aminohippuric acid (PAH) (22) and serum creatinine levels (23)] (see also ref. 24). This interpretation of the data does not exclude the possibility that the slit-diaphragm acts as a molecular sieve, but it questions whether this action is required.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing GFR in those studies was similar to the trends observed in the current study. In humans, the GFR is 2–4 mL/min/1.73 m 2 at birth, increases rapidly to 39–47 mL/min/1.73 m 2 during the first 2 weeks of life, continues rising to 58–103 mL/min/m 2 during the first year of life and reaches adult values (127 mL/min/1.73 m 2 ) at the age of 2 years (Guignard et al, 1975; Heilbron et al, 1991). The age correlations between humans and pigs proposed by Gad (2007) were considered here to compare the GFR between humans and piglets, namely neonate (human: 0–28 days, pig: 0–15 days), infant (human: 1–23 months, pig: 2–4 weeks), child (human: 2–12 years, pig: 4–14 weeks) and adolescent (human: 12–16 years, pig: 4–6 months).…”
Section: Discussionmentioning
confidence: 99%
“…9 In children, there is also a maturational increase in GFR beginning at birth when it is very low (~20 mL/min/1.73 m 2 ) and ultimately culminating in the adult level of ~120 mL/min/1.73 m 2 by approximately 2 years of age. 10 …”
Section: Assessment Of Glomerular Functionmentioning
confidence: 99%